PERANCANGAN APLIKASI DESKTOP SISTEM INFORMASI GEOGRAFIS (SIG) PENYEBARAN WISATA KULINER DI KOTA BANDAR LAMPUNG - Kurnia Muludi; Astria Hijriani; Khalida Zhia (Universitas Lampung, 2014)
People need more information about geographical related objects, for example: distance between regions, object locations, facilities, natural resources etc. Geographic Information System (GIS) is a solution for getting information on geographical related objects. The object of this research is Lampung culinary, because Lampung Province has many typical foods and many culinary places for young people, teenagers, and parents to gather. That culinary places can be categorized as café, restaurant, and many more. This application is developed using Microsoft Visual Basic Express 2010 and MapWinGIS ActiveX Control. The development of this application implement Water Fall method. Other supporting softwares are My GPS Coordinates, Quantum GIS, and Microsoft Access Database.